Anomalies in the rabies indirect fluorescent antibody test confound accurate antemortem diagnosis of human rabies - Rudd, R. J.; Wong, S. J.; Appler, K. K. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
The antemortem diagnosis of rabies in humans employs techniques that require accuracy, speed and sensitivity. A combination of histochemical, in vitro virus isolation, immunologic and molecular amplification procedures are utilized in an effort to diagnose the disease. Present day technology offers a potentially life-saving treatment for a disease that was considered invariably fatal once clinical signs develop. This new development adds to the need for a rapid diagnosis as early in the course of clinical signs as possible. The techniques offering diagnosis within hours are the direct fluorescent antibody test on skin and the indirect fluorescent antibody procedure on cerebral spinal fluid and serum. We describe examination by indirect fluorescent antibody assay of cerebral spinal fluid and serum taken from patients with viral encephalitis or a presumed viral infection from an agent other than rabies virus. A total of 135 CSF samples from viral encephalitis patients were tested by the rabies indirect fluorescent antibody procedure. A majority of the spinal fluids tested, from patients with encephalitis, presented immunoglobulins that bound to antigens present in cell culture substrate. Most notable were the reactions on kidney cells provided from sera or spinal fluid obtained from patients diagnosed with the flavivirus infections Powassan Virus or West Nile Virus. The majority of reaction patterns were recognizably different than what is seen with specific anti-rabies antibodies. However, results indicate that false positive results could occur when interpreting the rabies indirect fluorescent antibody procedure. A staining pattern appearing similar to specific anti-rabies staining was observed in 7 of the 135 spinal fluids examined. The potential for false positive results documented in this work offers weight to the argument that tandem positive results from two diagnostic test platforms are essential when diagnosing rabies in the human patient.